John Bull’s Adventures in the Fiscal Wonderland : Rhétorique graphique et propagande politique dans la controverse fiscale 1903-1910 - Philippe Vervaecke (Revue LISA)
This article deals with the pictorial propaganda produced by protectionist and free-trade pressure groups between 1903 and 1910. The Tariff Reform controversy, which opposed Liberals and Conservatives during the Edwardian era, has been extensively covered, but the massive use of pictorial propaganda by both sides has been largely neglected as a historical source. The article first focuses on the fears expressed by many Edwardian observers about the advent of pictorial propaganda, often seen by them as the intrusion of irrationality into politics. It then delineates the rhetoric displayed by protectionist and free-trade pictorial propaganda and the consistency of their respective viewpoints of British society and of the international context. It finally claims that pictorial propaganda, far from subverting democracy and politics, sought to uphold established norms of rational, manly and independent citizenship.